A wear-resistant and corrosion-resistant plastic and its preparation method and application

By adding carbon nanofibers and ethylenediamine-modified WS2 nanosheets to polyetherimide plastics, the shortcomings of polyetherimide plastics in terms of mechanical properties and wear resistance are solved, and high wear and corrosion resistance are achieved.

CN118063963BActive Publication Date: 2025-04-25SHANGHAI DYNACHEM COMPOUND PLASTIC CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410183856.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-19
Publication Date
2025-04-25
Estimated Expiration
2044-02-19

AI Technical Summary

Technical Problem

The existing polyetherimide plastics have shortcomings in terms of mechanical properties and wear resistance, and it is difficult to meet the needs of high wear resistance and corrosion resistance.

Method used

The mechanical properties and wear resistance of the plastic are improved by adding carbon nanofibers and ethylenediamine-modified WS2 nanosheets. Carbon nanofibers improve the mechanical properties of plastics, while ethylenediamine-modified WS2 nanosheets promote their uniform distribution in the substrate, enhancing the plastic's wear and corrosion resistance.

Benefits of technology

It significantly improves the wear and corrosion resistance of polyetherimide plastics, with good mechanical properties and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004991067280000081
    Figure GDA0004991067280000081
  • Figure GDA0004991067280000091
    Figure GDA0004991067280000091
Patent Text Reader

Abstract

The present invention belongs to the field of plastic technology, and specifically relates to a wear-resistant and corrosion-resistant plastic and a preparation method and application thereof. The wear-resistant and corrosion-resistant plastic provided by the present invention comprises the following components by weight: 100 parts of polyetherimide; 2 to 4 parts of lubricant; 10 to 20 parts of carbon nanofibers; and 2 to 4 parts of ethylenediamine-modified WS2 nanosheets. By adding carbon nanofibers and ethylenediamine-modified WS2 nanosheets, the wear resistance, corrosion resistance and corrosion resistance of the plastic can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of plastics, and more specifically, relates to a wear-resistant and corrosion-resistant plastic and a preparation method and application thereof. Background Art

[0002] Polyetherimide (PEI) is a transparent amber amorphous new high-performance thermoplastic resin. Its molecular structure contains both aromatic amine functional groups and ether structures. Therefore, it not only has high temperature resistance, high strength, high modulus, high insulation and corrosion resistance, but also has good dimensional stability and good processing performance. It can be formed by traditional extrusion, injection molding and other processes, and its price is relatively low. The glass transition temperature (Tg) of PEI is 215℃, and it can be used continuously in an environment with a temperature of about 170℃. It has excellent flame retardant properties (oxygen index>47), high toughness and radiation resistance, and excellent chemical resistance. It can withstand various acids, alkalis and organic solvents, can pass microwaves and has good dielectric properties. As a substitute for traditional metals, it has been used in military equipment, aerospace, automobiles, electronics, machinery, chemicals and other fields.

[0003] CN117050461A discloses a peek plastic board preparation formula and preparation method thereof. The peek plastic board preparation formula of the present application includes the following weight parts: 80-120 parts of polyetheretherketone, 10-20 parts of polyetherimide, 1-8 parts of basalt fiber, 3-7 parts of modifier, 1-4 parts of nano-sepiolite, and 4-6 parts of auxiliary agent; the modifier is obtained by mixing magnesium hydroxide coated with lanthanum diethylenetriamine penta (methylenephosphonate) and octaaminophenyl silsesquioxane in a mass ratio of 2-8:1; the present application performs plasma pretreatment on polyetheretherketone, polyetherimide, and basalt fiber, then adds modifier, nano-sepiolite, and auxiliary agent, mixes evenly, extrude, and mold to obtain peek plastic board, which has simple steps, low cost, and is suitable for industrial production. The obtained peek plastic board will not emit harmful gases during combustion, nor will it cause secondary combustion due to the melting drop phenomenon, and has broad market prospects.

[0004] CN114806168A discloses a material formula for a hollow plastic eyeglass frame, wherein the raw materials include, by weight percentage: 60-80% polyetherimide, 10-20% polyphenylene sulfone resin, 10%-20% polyether sulfone resin, 2-3% short glass fiber, 2-3% carbon fiber or 2-3% nano calcium carbonate, and 0-1% epichlorohydrin. The invention uses polyetherimide (PEI) as the base material of the eyeglasses, and improves the strength of the hollow part of the material by strengthening and toughening the PEI; and combines the hollow plastic eyeglasses mold with the injection molding process optimization to improve the problem of poor fluidity of the plastic solution at the hollow part of the eyeglasses during the injection molding process, thereby realizing the production of high-quality hollow eyeglasses and meeting the market demand for high-quality hollow plastic eyeglasses.

[0005] CN107400352A discloses a heat-resistant insulating plastic for electronics, which contains the following components by mass: 50-80 parts of polycarbonate; 25-45 parts of base resin; 10-15 parts of polyetherimide; 10-15 parts of SBS thermoplastic elastomer; 3.5-6 parts of PPO-g-MAH; 50-60 parts of magnesium oxide; 20-30 parts of aluminum oxide; 0.3-0.6 parts of paraffin wax; 0.4-0.8 parts of bisphenol A; 5-10 parts of toughening agent; 1.2-4.5 parts of tribasic lead sulfate. The advantages of the present invention are: the heat-resistant insulating plastic for electronics provided by the present invention and the preparation method thereof have strong impact resistance, high heat resistance and insulation performance, and high toughness, and are very suitable for use in electronic products with high electronic circuit integration.

[0006] TW201823360A discloses a plastic composition and a preparation method thereof. The plastic composition comprises about 98.5 to 99.995 parts by weight of a base material powder, about 0.005 to 1 parts by weight of a carbon black powder, and about 0.00025 to 0.5 parts by weight of a solid dispersant. The base material powder comprises polyetherimide. The particle size of the carbon black powder is less than or equal to about 500 nanometers. An optical element made using the plastic composition is also provided.

[0007] It can be seen that the existing polyetherimide is added as a modified component to other base materials. The polyetherimide itself has corrosion resistance, but there are still deficiencies in improving the mechanical properties and wear resistance of the polyetherimide. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a wear-resistant and corrosion-resistant plastic and its preparation method and application. The wear-resistant and corrosion-resistant plastic provided by the present invention comprises the following components by weight: 100 parts of polyetherimide; 2 to 4 parts of lubricant; 10 to 20 parts of carbon nanofibers; and 2 to 4 parts of ethylenediamine-modified WS2 nanosheets. By adding carbon nanofibers and ethylenediamine-modified WS2 nanosheets, the wear resistance, corrosion resistance and corrosion resistance of the plastic can be improved.

[0009] The purpose of the present invention is to provide a wear-resistant and corrosion-resistant plastic.

[0010] Another object of the present invention is to provide a method for preparing the wear-resistant and corrosion-resistant plastic.

[0011] Another object of the present invention is to provide an application of wear-resistant and corrosion-resistant plastics.

[0012] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0013] A wear-resistant and corrosion-resistant plastic, comprising the following components in parts by weight:

[0014] Polyetherimide: 100 parts;

[0015] 2 to 4 parts of lubricant;

[0016] 10-20 parts of carbon nanofiber;

[0017] 2 to 4 parts of WS2 nanosheets modified with ethylenediamine.

[0018] Preferably, the lubricant is pentaerythritol stearate; the length of the carbon nanofibers is 1 to 3 mm, and the aspect ratio is 50 to 100:1.

[0019] In the present invention, the preferred technical solution is that the preparation method of the ethylenediamine-modified WS2 comprises the following steps:

[0020] (1) Preparation of WS2 nanosheets: ammonium tungstate, oxalic acid and thiourea were mixed and ultrasonically dispersed in deionized water. After hydrothermal reaction, the product was washed and dried to obtain WS2 nanosheets.

[0021] (2) Carboxylation of WS2 nanosheets: ultrasonically dispersing WS2 nanosheets in deionized water, then adding bromoacetic acid, stirring to react, filtering, washing, and drying to obtain carboxyl-modified WS2 nanosheets;

[0022] (3) Ultrasonic dispersion of the carboxyl-modified WS2 nanosheets and ethylenediamine prepared in step (2) into an appropriate amount of ethanol water, heating to 40-80° C. and stirring for reaction for 2-4 h. After the reaction is completed, washing is performed to obtain ethylenediamine-modified WS2.

[0023] Preferably, in step (1), the molar ratio of ammonium tungstate, oxalic acid and thiourea is 1:2:5; and the hydrothermal condition is 180-220° C. for 20-30 hours.

[0024] Further preferably, in step (1), the drying is performed at 80° C. to constant weight.

[0025] Preferably, in step (2), the stirring reaction is carried out at 50-70° C. for 10-20 h; and the drying is carried out at 80-120° C. for 6-12 h.

[0026] Further preferably, in step (2), the molar ratio of the WS2 nanosheets to bromoacetic acid is 1:11-13.

[0027] Preferably, in step (3), the volume ratio of ethanol to water is 3:1; the mass ratio of the carboxyl-modified WS2 nanosheets to ethylenediamine is 1:1-2.

[0028] Based on the above-mentioned method for preparing a wear-resistant and corrosion-resistant plastic, the preparation method comprises the following steps:

[0029] (1) placing polyetherimide in a vacuum drying oven at 120-160° C. and drying for 3-5 hours, then adding polyetherimide, lubricant, carbon nanofiber and ethylenediamine-modified WS2 nanosheets into a high-speed stirrer and stirring at a speed of 4000-5000 rpm for 20-40 minutes;

[0030] (2) adding the above-mentioned materials which have been stirred evenly into the hopper of a parallel twin-screw extruder, setting the temperatures of the heating sections of the extruder from the hopper to the die head to 265-285° C., 305-315° C., 325-345° C., 325-345° C., 325-345° C., 345-355° C., respectively, the screw speed of the main machine to 280-340 r / min, the screw speed of the hopper feed screw to 20-40 r / min, and then blending and melting the materials to extrude pellets;

[0031] (3) The pellets coming out of the extruder die are transported to a pelletizer through a steel conveyor belt for pelletizing to obtain a highly wear-resistant polyetherimide composite material with a length of 3 to 5 mm.

[0032] The wear-resistant and corrosion-resistant plastic described above is applied to the mechanical field or the chemical field.

[0033] The present invention has the following beneficial effects:

[0034] (1) WS2 is modified by ethylenediamine, which can promote its uniform distribution in the substrate, and the interface distribution is uniform, with strong bonding ability, which can greatly improve the wear resistance and corrosion resistance of the plastic.

[0035] (2) By adding carbon nanofibers, the mechanical properties of plastics can be improved, as well as the wear resistance of plastics.

[0036] (3) The plastic prepared by the present invention has good wear resistance and corrosion resistance and has a good application prospect. DETAILED DESCRIPTION

[0037] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0038] Polyetherimide: Product number, PEI 1000-1000.

[0039] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0040] Example 1

[0041] A wear-resistant and corrosion-resistant plastic, comprising the following components in parts by weight:

[0042] Polyetherimide: 100 parts;

[0043] 3 parts of lubricant; the lubricant is pentaerythritol stearate;

[0044] 15 parts of carbon nanofibers; the length of the carbon nanofibers is 2 mm, and the aspect ratio is 80:1;

[0045] 3 parts of ethylenediamine-modified WS2 nanosheets;

[0046] The preparation method of ethylenediamine-modified WS2 comprises the following steps:

[0047] (1) Preparation of WS2 nanosheets: 1 mol of ammonium tungstate, 2 mol of oxalic acid and 5 mol of thiourea were mixed and ultrasonically dispersed in 200 mL of deionized water. After hydrothermal reaction at 200 °C for 26 h, the product was washed and dried at 80 °C to constant weight to obtain WS2 nanosheets.

[0048] (2) Carboxylation of WS2 nanosheets: 1 mol of WS2 nanosheets was ultrasonically dispersed in 150 mL of deionized water, and then 12 mol of bromoacetic acid was added, stirred at 60 °C for 16 h, filtered, washed, and dried at 100 °C for 10 h to obtain carboxyl-modified WS2 nanosheets;

[0049] (3) Ultrasonic dispersion of 100 g of the carboxyl-modified WS2 nanosheets prepared in step (2) and 150 g of ethylenediamine in an appropriate amount of ethanol water (the volume ratio of ethanol to water is 3:1), heating to 60°C and stirring for reaction for 3 h. After the reaction is completed, washing and drying at 60°C to constant weight to obtain ethylenediamine-modified WS2.

[0050] A method for preparing wear-resistant and corrosion-resistant plastics comprises the following steps:

[0051] (1) placing polyetherimide in a vacuum drying oven at 140° C. and drying for 4 hours, then adding polyetherimide, lubricant, carbon nanofibers and ethylenediamine-modified WS2 nanosheets into a high-speed stirrer and stirring at a speed of 4500 rpm for 30 minutes;

[0052] (2) adding the above-mentioned materials that have been stirred evenly into the hopper of a parallel twin-screw extruder, setting the temperatures of the heating sections of the extruder from the hopper to the die head to 275° C., 310° C., 335° C., 335° C., 335° C., 350° C., respectively, the screw speed of the main machine to 320 r / min, the screw speed of the hopper feed screw to 30 r / min, and then blending and melting the materials to extrude pellets;

[0053] (3) The pellets coming out of the extruder die are transported to a pelletizer through a steel conveyor belt for pelletizing to obtain a highly wear-resistant polyetherimide composite material with a length of 4 mm.

[0054] Example 2

[0055] A wear-resistant and corrosion-resistant plastic, comprising the following components in parts by weight:

[0056] Polyetherimide: 100 parts;

[0057] 4 parts of lubricant; the lubricant is pentaerythritol stearate;

[0058] 10 parts of carbon nanofibers; the length of the carbon nanofibers is 3 mm, and the aspect ratio is 100:1;

[0059] 4 parts of WS2 nanosheets modified with ethylenediamine;

[0060] The preparation method of ethylenediamine-modified WS2 comprises the following steps:

[0061] (1) Preparation of WS2 nanosheets: The same as the preparation of WS2 nanosheets in step (1) in Example 1.

[0062] (2) Carboxylation of WS2 nanosheets: 1 mol of WS2 nanosheets was ultrasonically dispersed in 150 mL of deionized water, and then 13 mol of bromoacetic acid was added, stirred at 70 °C for 10 h, filtered, washed, and dried at 120 °C for 6 h to obtain carboxyl-modified WS2 nanosheets;

[0063] (3) 100 g of the carboxyl-modified WS2 nanosheets prepared in step (2) and 200 g of ethylenediamine are ultrasonically dispersed in an appropriate amount of ethanol water (the volume ratio of ethanol to water is 3:1), the temperature is raised to 80°C and stirred for reaction for 2 h. After the reaction is completed, the WS2 modified with ethylenediamine is washed and dried at 60°C to constant weight to obtain.

[0064] A method for preparing wear-resistant and corrosion-resistant plastics comprises the following steps:

[0065] (1) placing polyetherimide in a vacuum drying oven at 160° C. and drying for 3 hours, then adding polyetherimide, lubricant, carbon nanofibers and ethylenediamine-modified WS2 nanosheets into a high-speed stirrer and stirring at a speed of 5000 rpm for 20 minutes;

[0066] (2) adding the above-mentioned materials that have been stirred evenly into the hopper of a parallel twin-screw extruder, setting the temperatures of the heating sections of the extruder from the hopper to the die head to 285° C., 305° C., 325° C., 325° C., 325° C., and 345° C., respectively, the screw speed of the main machine is 340 r / min, and the speed of the hopper feed screw is 20 r / min, and then the materials are blended and melted to extrude pellets;

[0067] (3) The pellets coming out of the extruder die are transported to a pelletizer through a steel conveyor belt for pelletizing to obtain a highly wear-resistant polyetherimide composite material with a length of 5 mm.

[0068] Example 3

[0069] A wear-resistant and corrosion-resistant plastic, comprising the following components in parts by weight:

[0070] Polyetherimide: 100 parts;

[0071] 4 parts of lubricant; the lubricant is pentaerythritol stearate;

[0072] 10 parts of carbon nanofibers; the length of the carbon nanofibers is 1 mm, and the aspect ratio is 50:1;

[0073] 4 parts of WS2 nanosheets modified with ethylenediamine;

[0074] The preparation method of ethylenediamine-modified WS2 comprises the following steps:

[0075] (1) Preparation of WS2 nanosheets: The same as the preparation of WS2 nanosheets in step (1) in Example 1.

[0076] (2) Carboxylation of WS2 nanosheets: 1 mol of WS2 nanosheets was ultrasonically dispersed in 150 mL of deionized water, and then 11 mol of bromoacetic acid was added, stirred at 50 °C for 20 h, filtered, washed, and dried at 80 °C for 12 h to obtain carboxyl-modified WS2 nanosheets;

[0077] (3) Ultrasonic dispersion of 100 g of the carboxyl-modified WS2 nanosheets prepared in step (2) and 100 g of ethylenediamine in an appropriate amount of ethanol water (the volume ratio of ethanol to water is 3:1), heating to 40°C and stirring for reaction for 4 h. After the reaction is completed, washing and drying at 60°C to constant weight to obtain ethylenediamine-modified WS2.

[0078] A method for preparing wear-resistant and corrosion-resistant plastics comprises the following steps:

[0079] (1) placing polyetherimide in a vacuum drying oven at 120° C. and drying for 5 hours, then adding polyetherimide, lubricant, carbon nanofibers and ethylenediamine-modified WS2 nanosheets into a high-speed stirrer and stirring at a speed of 4000 rpm for 40 minutes;

[0080] (2) adding the above-mentioned materials that have been stirred evenly into the hopper of a parallel twin-screw extruder, setting the temperatures of the heating sections of the extruder from the hopper to the die head to 265° C., 315° C., 345° C., 345° C., 345° C., and 355° C., respectively, setting the screw speed of the main machine to 280 r / min, and the screw speed of the hopper feed screw to 40 r / min, and then blending and melting the materials to extrude pellets;

[0081] (3) The pellets coming out of the extruder die are transported to a pelletizer through a steel conveyor belt for pelletizing to obtain a highly wear-resistant polyetherimide composite material with a length of 3 mm.

[0082] Comparative Example 1

[0083] The method is basically the same as Example 1, except that the ethylenediamine-modified WS2 nanosheets are not modified with ethylenediamine; and the preparation method of WS2 comprises the following steps:

[0084] (1) Preparation of WS2 nanosheets: The same as the preparation of WS2 nanosheets in Example 1.

[0085] (2) Carboxylation of WS2 nanosheets: 1 mol of WS2 nanosheets was ultrasonically dispersed in 150 mL of deionized water, and then 13 mol of bromoacetic acid was added, stirred at 70 °C for 10 h, filtered, washed, and dried at 120 °C for 6 h to obtain carboxyl-modified WS2 nanosheets.

[0086] Comparative Example 2

[0087] The method is basically the same as Example 1, except that the ethylenediamine-modified WS2 nanosheets are not modified with ethylenediamine; and the preparation method of WS2 comprises the following steps:

[0088] Preparation of WS2 nanosheets: The same as the preparation of WS2 nanosheets in step (1) in Example 1.

[0089] Comparative Example 3

[0090] A wear-resistant and corrosion-resistant plastic, comprising the following components in parts by weight:

[0091] Polyetherimide: 100 parts;

[0092] 3 parts of lubricant; the lubricant is pentaerythritol stearate;

[0093] 18 parts of carbon nanofibers; the length of the carbon nanofibers is 2 mm, and the aspect ratio is 80:1;

[0094] A method for preparing wear-resistant and corrosion-resistant plastics comprises the following steps:

[0095] (1) placing the polyetherimide in a vacuum drying oven at 140° C. and drying for 4 hours, then adding the polyetherimide, lubricant and carbon nanofiber into a high-speed stirrer and stirring at a speed of 4500 rpm for 30 minutes;

[0096] (2) adding the above-mentioned materials that have been stirred evenly into the hopper of a parallel twin-screw extruder, setting the temperatures of the heating sections of the extruder from the hopper to the die head to 275° C., 310° C., 335° C., 335° C., 335° C., 350° C., respectively, the screw speed of the main machine to 320 r / min, the screw speed of the hopper feed screw to 30 r / min, and then blending and melting the materials to extrude pellets;

[0097] (3) The pellets coming out of the extruder die are transported to a pelletizer through a steel conveyor belt for pelletizing to obtain a highly wear-resistant polyetherimide composite material with a length of 4 mm.

[0098] Comparative Example 4

[0099] A wear-resistant and corrosion-resistant plastic, comprising the following components in parts by weight:

[0100] Polyetherimide: 100 parts;

[0101] 3 parts of lubricant; the lubricant is pentaerythritol stearate;

[0102] 18 parts of ethylenediamine-modified WS2 nanosheets;

[0103] The preparation method of ethylenediamine-modified WS2 comprises the following steps:

[0104] (1) Preparation of WS2 nanosheets: 1 mol of ammonium tungstate, 2 mol of oxalic acid and 5 mol of thiourea were mixed and ultrasonically dispersed in 200 mL of deionized water. After hydrothermal reaction at 200 °C for 26 h, the product was washed and dried at 80 °C to constant weight to obtain WS2 nanosheets.

[0105] (2) Carboxylation of WS2 nanosheets: 1 mol of WS2 nanosheets was ultrasonically dispersed in 150 mL of deionized water, and then 12 mol of bromoacetic acid was added, stirred at 60 °C for 16 h, filtered, washed, and dried at 100 °C for 10 h to obtain carboxyl-modified WS2 nanosheets;

[0106] (3) Ultrasonic dispersion of 100 g of the carboxyl-modified WS2 nanosheets prepared in step (2) and 150 g of ethylenediamine in an appropriate amount of ethanol water (the volume ratio of ethanol to water is 3:1), heating to 60°C and stirring for reaction for 3 h. After the reaction is completed, washing and drying at 60°C to constant weight to obtain ethylenediamine-modified WS2.

[0107] A method for preparing wear-resistant and corrosion-resistant plastics comprises the following steps:

[0108] (1) placing polyetherimide in a vacuum drying oven at 140° C. and drying for 4 hours, then adding polyetherimide, lubricant and ethylenediamine-modified WS2 nanosheets into a high-speed stirrer and stirring at a speed of 4500 rpm for 30 minutes;

[0109] (2) adding the above-mentioned materials that have been stirred evenly into the hopper of a parallel twin-screw extruder, setting the temperatures of the heating sections of the extruder from the hopper to the die head to 275° C., 310° C., 335° C., 335° C., 335° C., 350° C., respectively, the screw speed of the main machine to 320 r / min, the screw speed of the hopper feed screw to 30 r / min, and then blending and melting the materials to extrude pellets;

[0110] (3) The pellets coming out of the extruder die are transported to a pelletizer through a steel conveyor belt for pelletizing to obtain a highly wear-resistant polyetherimide composite material with a length of 4 mm.

[0111] The mechanical properties and wear resistance of Examples 1-3 and Comparative Examples 1-4 were tested. The specific test results are shown in Table 1.

[0112] Among them: bending strength GB / T9341-2000;

[0113] Friction coefficient: GB / T3960-1983.

[0114] Table 1:

[0115]

[0116]

[0117] From the data in Table 1, in the present invention, WS2 can be modified by ethylenediamine to improve the wear resistance and corrosion resistance of plastics. The addition of carbon nanofibers can improve the mechanical properties of plastics, improve the wear resistance of plastics, etc. In summary, the wear-resistant and corrosion-resistant plastic prepared by the present invention has good mechanical properties and wear resistance.

[0118] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A wear-resistant and corrosion-resistant plastic, characterized in that: By weight, it is prepared from the following components: Polyetherimide: 100 parts; 3 parts of lubricant; the lubricant is pentaerythritol stearate; 15 parts of carbon nanofibers; the length of the carbon nanofibers is 2 mm, and the aspect ratio is 80:1; 3 parts of ethylenediamine-modified WS2 nanosheets; The preparation method of ethylenediamine-modified WS2 comprises the following steps: (1) Preparation of WS2 nanosheets: 1 mol of ammonium tungstate, 2 mol of oxalic acid and 5 mol of thiourea were mixed and ultrasonically dispersed in 200 mL of deionized water. After hydrothermal reaction at 200 °C for 26 h, the product was washed and dried at 80 °C to constant weight to obtain WS2 nanosheets. (2) Carboxylation of WS2 nanosheets: 1 mol of WS2 nanosheets was ultrasonically dispersed in 150 mL of deionized water, and then 12 mol of bromoacetic acid was added, stirred at 60 °C for 16 h, filtered, washed, and dried at 100 °C for 10 h to obtain carboxyl-modified WS2 nanosheets; (3) 100 g of the carboxyl-modified WS2 nanosheets prepared in step (2) and 150 g of ethylenediamine were ultrasonically dispersed in an appropriate amount of ethanol and water, wherein the volume ratio of ethanol to water was 3:1, and the temperature was raised to 60°C and stirred for reaction for 3 h. After the reaction was completed, the WS2 modified with ethylenediamine was washed and dried at 60°C to constant weight to obtain; The preparation method of the wear-resistant and corrosion-resistant plastic comprises the following steps: (1) The polyetherimide was placed in a vacuum drying oven at 140°C and dried for 4 hours, and then the polyetherimide, lubricant, carbon nanofibers and ethylenediamine-modified WS2 nanosheets were added to a high-speed mixer and stirred at a speed of 4500 rpm for 30 minutes; (2) Add the above-mentioned materials that have been stirred evenly into the hopper of a parallel twin-screw extruder, set the temperatures of the heating sections of the extruder from the hopper to the die head to 275°C, 310°C, 335°C, 335°C, 350°C, respectively, set the screw speed of the main machine to 320 r / min, and the screw speed of the hopper feed screw to 30 r / min, and then blend and melt the materials to extrude pellets; (3) The pellets coming out of the extruder die are transported to a pelletizer through a steel conveyor belt for pelletizing to obtain wear-resistant and corrosion-resistant plastics with a length of 4 mm.

Citation Information

Patent Citations

  • Heat-resistant insulating plastics for electronics

    CN107400352A

  • Plastic composition and preparaiton method thereof and optical device using the same

    TW201823360A

  • Wear-resistant self-lubricating thermoplastic polyimide composite material and preparation method thereof

    CN109705576A

  • Composite material for sliding wear-resisting plate of bridge support and preparation method of composite material

    CN115536928A